Factors Influencing Postnatal Care Utilization in Lumbini Province, Nepal - Devkota, Bijaya Mani (Cognition, 2026)
Postnatal period is the most critical period of maternal health continuum, which contributes a vast proportion of both maternal and neonatal. Though Nepal has improved its coverage of maternal health services, the coverage of postnatal care (PNC) is not evenly spread across the population groups and provinces. The targeted planning and equal distribution of resources require evidence at the province level. This study presents the use of postnatal care in the 48 hours after delivery, and its important determinants among women in the Lumbini Province. Demographic and Health Survey (NDHS) 2022; used as a sample of 481 women aged 1549 years with a live birth within the five years before the survey and full data on early PNC that had a stratified two-stage cluster sampling scheme. Socio-demographic and reproductive factors were subjected to weighted descriptive statistics, bivariate analysis and bivariate logistic regression. Women who had postnatal care in 48 hours had a 76.3 percent and those who did not had 23.7 percent. Birth order became the most important determinant: women of second and third-or-more births were much less likely to receive early PNC than first-time mothers (OR = 0.51 and OR = 0.25). There was also large age, caste/ethnicity, education, wealth status and residence differences. Nevertheless, there are still huge inequities even with utilization. Interventions should be equity-oriented targeting high-parity females, adolescents, marginalized castes, rural people, and poor households to enhance access to timely postnatal care.